Performance analysis of two WMN architectures by WMN-GA simulation system considering different distributions and transmission rates. (2018) - Matsuo, Keita; Cuka, Miralda; Inaba, Takaaki; Oda, Tetsuya; Barolli, Leonard; Barolli, Admir
In this paper, we evaluate the performance of two Wireless Mesh Network (WMN) architectures considering throughput, delay and fairness index metrics. For simulations, we used a Genetic Algorithm (GA)-based simulation system (called WMN-GA) and ns-3. We compare the performance for two architectures considering normal and uniform distributions, different transmission rates and OLSR protocol. The simulation results show that the throughput and delay are increased, but the fairness index is decreased with increasing of transmission rate. The throughput of Hybrid WMN is higher than Infrastructure/Backbone (I/B) WMN. But, the delay of I/B WMN is higher than Hybrid WMN for normal distribution. The fairness index of normal distribution is higher than uniform distribution.